1999
DOI: 10.1002/(sici)1097-4628(19990606)72:10<1241::aid-app2>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Plastic behavior of monoclinic polypropylene under hydrostatic pressure in compressive testing

Abstract: The plastic deformation of monoclinic isotactic polypropylene is studied in compressive testing with particular attention to the effect of hydrostatic pressure up to 300 MPa, in the temperature range 20 -60°C. The coefficients of the Coulomb criterion are fairly consistent with those assessed from the comparison of the tensile and compressive yield stresses at atmospheric pressure, in the same temperature range. The high friction coefficient of polypropylene is ascribed to a strain-induced order-todisorder tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Plasticity and yield of iPP have been the focus of attention in the past decade, see, e.g., ref. [1][2][3][4][5][6][7][8][9][10] This may be explained by numerous applications of poly(propylene) in industry (ranged from oriented films for packaging to nonwoven fabrics and reinforcing fibres).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Plasticity and yield of iPP have been the focus of attention in the past decade, see, e.g., ref. [1][2][3][4][5][6][7][8][9][10] This may be explained by numerous applications of poly(propylene) in industry (ranged from oriented films for packaging to nonwoven fabrics and reinforcing fibres).…”
Section: Introductionsupporting
confidence: 82%
“…The latter case, however, is excluded from the consideration in this work, because it requires the mathematical apparatus of finite deformations to be used (at e > e y ¼ 0.13, Equation (1), (2) and (9) become inapplicable). Equation (7), (8) and (14) …”
Section: Constitutive Equationsmentioning
confidence: 99%
“…An important advantage of the stress-strain relations (1), (2), (4) to (6), (15) and (19) is that 3 constants, E 0 , a and ε, are found by fitting experimental data for the loading path of a stress-strain curve, whereas the other two parameters, K and κ, are determined by matching observations for the unloading path.…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…An attempt can be made to approach the plastic deformation kinetics of isotactic PP in a way similar to that developed for PE. The plastic behavior of PP in its stable monoclinic crystalline form in terms of crystal slip and dislocation activation has been specifically addressed by several authors 14, 15, 29, 54–56. Experimental and theoretical investigations of the molecular mobility in the crystal have shown that the basic motion of the chain stems with a 3/1 helix conformation is a threefold rotation about the stem axis accompanied by a c /3 translation parallel to the stem axis 46, 57.…”
Section: Case Of Ppmentioning
confidence: 99%
“…As for PE, the PP stems cannot rotate and translate as a rigid entity but should rather involve the migration of a conformational defect 41. However, only hypotheses have been put forward regarding the nature of the mobile defect 56…”
Section: Case Of Ppmentioning
confidence: 99%